MATERIALISME DALAM TAFSIR SAYYID QUTB: Studi Atas Q.S Ali Imran Ayat 14 - Utami, Devi Aulia; Rusli, Ris’an; Farsyad, Ahmad Farid (TAJDID: Jurnal Ilmu Ushuluddin, 2024)
This article discusses Sayyid Qutb's views on materialism, especially in the context of his interpretation of Surah Ali Imran, verse 14. This verse mentions human love for the world, including wealth, women, children, and other worldly pleasures. The method used in this article is a qualitative approach with a literature review. For the analytical approach, the article employs a tahlili (analytical) method, which allows the author to explore a verse in-depth. Through this study, the article aims to reveal how Qutb's *Tafsir Fi Zhilalil Qur'an* provides relevant insights into the dangers of materialism in modern life and how Muslims should balance their worldly life with the hereafter. The research findings show that in his tafsir, Sayyid Qutb criticizes excessive love for the world as a form of materialism that can divert Muslims from their higher purpose in life, which is to seek Allah’s pleasure and the happiness of the hereafter. Qutb emphasizes the importance of awareness that love for the world must remain within reasonable limits so that it does not hinder one's focus on spiritual values and righteous deeds.